42 1 year clinical outcomes following primary pci for stemi in post cardiac arrest patients, with comparison to an overall stemi population. (5th October 2017) - Wheen, P; Cadogan, D; McFadden, E
Abstract : Aims: To retrospectively review patients who presented with a STEMI to a primary PCI centre between 1st January 2015 and 31st December 2015, and assess their 1 year mortality, refractory angina, unplanned revascularisation and heart failure, and to compare these data with patients who underwent Primary PCI following cardiac arrest or required inotropic support during the procedure. Methods: We used the hospitals STEMI registry to obtain patient records for all patients who presented between 1st January 2015 and 31st December 2015 with a STEMI. We used the local electronic records to obtain details about the initial presentation and follow up details. Results: 178 patients, 36 female (20.2%) presented to our institution with a STEMI during the study period. Mean age (mean (+/- SD)) was 62.9 years +/- 12.6. Follow up was obtained on 62.4% of patients, with a mean follow up of 11.8 months (+/- 5.4). 95.0% of patients underwent successful primary PCI. At 1 year, overall rates of complications were as follows: death 11.7%, refractory angina 3.6%, unplanned revascularisation 4.5%, non fatal MI 4.5% and heart failure 17.1%. 10 patients (5.6%) presented following cardiac arrest. 3 (1.7%) additional patients were commenced on inotropes during Primary PCI. For primary PCI patients following cardiac arrest or with commencement of inotropic support, the rates of complications at one year were as follows: death 46.2%, refractory angina 0%, non fatal MI 0%, unplanned revascularisation 0%, heart failure 38.5%. Conclusions: Mortality post STEMI at one year remains high at 11.7%, rising up to 46.2% in patients post – arrest or requiring inotropic support. The most frequent complication encountered following STEMI is heart failure, which is more frequent in the post arrest patient cohort.